PENGARUH PENAMBAHAN FLY ASH TERHADAP KUALITAS SEMEN DI PT SEMEN BATURAJA TBK - Maghpiroh, Ana; Iskandar, Damayanti; anaser, Novadri; Tohir, Safaruddin (Jurnal Multidisipliner Bharasumba, 2023)
Fly Ash or fly ash is solid waste produced from burning coal in power plants. Fly Ash was previously obtained from the simple production of burning coal with a gas funnel and dispersed into the atmosphere. The use of Fly Ash on OPC type cement was carried out in this test with varying percentages of 2%, 4%, 6%, 8%, 10%, 12%, 14%. The test was carried out by adding an additive (Fly Ash) to the basic material for making OPC cement. Next, testing the chemical composition properties of Fly Ash using Xray, testing the physical properties of cement, namely testing the compressive strength resulting from molding the mortar and testing the setting time. Meanwhile, testing the chemical properties of cement was carried out using IR (insoluble residue) and SO3. From the results of this research, it was found that the addition of Fly Ash had a positive impact on 7 day compressive strength, setting time and SO3. The addition of Fly Ash from low to high percentages can increase the fineness of the cement so that it affects the setting time and compressive strength of the cement. From this research it was found that the addition of additives (Fly Ash) can improve the quality of OPC cement and in general it is not much different from the physical properties of PCC cement.